Temporal-oriented model of causal relationship for constructing explanations for decision-making process - Chalyi, Serhii; Leshchynskyi, Volodymyr (Національний технічний університет "Харківський політехнічний інститут", 2022)
The subject of research in the article is the decision-making process in intelligent systems. The goal is to develop a model of the causal relationship between the states of the decision-making process in an intelligent information system, taking into account the temporal aspect of this process, in order to build cause-and-effect relationships between the actions of the process and further use these dependencies to form explanations for the sequence of actions to obtain a decision. The formation of causal relations between the states of the decision-making process makes it possible to substantiate the sequence of actions of this process, considering incomplete information regarding external influences on this process. Tasks: structuring the decision-making process in an intelligent information system as a specialized business process; development of a three-element model of the causal relationship between the states of the decision-making process, considering the temporal aspect of this process; substantiation of the possibility of using three-element relationships to build causal dependencies for decision making in intelligent systems. The approaches used are: the set-theoretical approach used to describe the elements of the decision-making process in intelligent systems; a logical approach that provides a representation of the relationship between the states of the decision-making process; probabilistic approach to describe the probabilistic component of the decision-making process. The following results are obtained. The decision-making process in an intelligent information system was structured as a specialized business process that, using additional information from the user, turns the input data into a result that is valuable for this user; a three-element model of the causal relationship between the states of the decision-making process is proposed, which makes it possible to take into account external influences on the process; using a probabilistic approach, the possibility of using three-element causal relations to describe the decision-making process in intelligent systems is substantiated, taking into account uncontrolled external influences. Conclusions. The scientific novelty of the obtained results is as follows. A three-element model of the causal relationship between the states of the decision-making process is proposed, based on a model of a temporal rule of the "future" type, containing a state-cause, a state-effect and an intermediate state that reflects external influences. The model makes it possible to build a base of causeand-effect dependencies for the decision-making process in an intelligent information system, considering external influences and use these dependencies to build explanations for this process.

Предметом вивчення в статті є процес прийняття рішення в інтелектуальних системах. Метою є розробка моделі каузального відношення між станами процесу прийняття рішення в інтелектуальній інформаційній системі з урахуванням темпорального аспекту даного процесу з тим, щоб побудувати причинно-наслідкові залежності між діями процесу та в подальшому використати ці залежності для формування пояснень щодо послідовності дій з отримання рішення. Формування каузальних відношень між станами процесу прийняття рішення дає можливість обґрунтувати послідовність дій даного процесу з урахуванням неповної інформації щодо зовнішніх впливів на даний процес. Завдання: структуризація процесу прийняття рішень в інтелектуальній інформаційній системі як спеціалізованого бізнес-процесу; розробка трьохелементної моделі каузального відношення між станами процесу прийняття рішення з урахуванням темпорального аспекту даного процесу; обґрунтування можливості використання трьохелементних відношень для побудови каузальних залежностей для процесу прийняття рішення в інтелектуальних системах. Використовуваними підходами є: теоретико-множинний підхід, який застосовується для опису елементів процесу прийняття рішення в інтелектуальних системах; логічний підхід, який забезпечує представлення відношень між станами процесу прийняття рішення; ймовірнісний підхід для опису ймовірнісної складової процесу прийняття рішення. Отримані наступні результати. Виконано структуризацію процесу прийняття рішень в інтелектуальній інформаційній системі як спеціалізованого бізнес-процесу, який, з використанням додаткової інформації від користувача, перетворює вхідні дані у результат, що становлять цінність для цього користувача; запропоновано трьохелементну модель каузального відношення між станами процесу прийняття рішення, що дає можливість врахувати зовнішні впливи на процес; з використанням ймовірнісного підходу обґрунтовано можливість використання трьохелементних каузальних відношень для опису процесу прийняття рішення в інтелектуальних системах з урахуванням неконтрольованих зовнішніх впливів. Висновки. Наукова новизна отриманих результатів полягає в наступному. Запропоновано трьохелементну модель каузального відношення між станами процесу прийняття рішення, що базується на моделі темпорального правилу типу "future", містить стан-причину, стан-наслідок та проміжний стан, що відображає зовнішні впливи. Модель дає можливість побудувати базу причинно наслідкових залежностей для процесу прийняття рішення в інтелектуальній інформаційній системі з урахуванням зовнішніх впливів та використати ці залежності для побудови пояснень щодо даного процесу.
Темпорально-орієнтована модель каузального відношення для побудови пояснень щодо процесу прийняття рішення
Keywords: intellectual system; explanation; decision-making process; temporality; causality; інтелектуальна система; пояснення; процес прийняття рішення; темпоральність; причиннонаслідковий зв'язок